Changes in axial length in anisometropic children wearing orthokeratology lenses - Qin, Jian; Qing, Huiling; Ji, Na; Lyu, Tianbin; Ma, Hui; Shi, Menghai; Yu, Shiao; Ma, Conghui; Fu, Aicun (Frontiers in Medicine, 2023)
Purpose: There is a particular anisometropia occurring in one eye with myopia, while the other eye has very low myopia, emmetropia or very low hyperopia. It is unclear how the binocular axial length changes when these children wear the unilateral OK lenses only in the more myopic eyes. This study investigates the changes in axial elongation of the both eyes.Methods: One-year retrospective study. 148 children with myopic anisometropia were included. The more myopic eyes were wearing the orthokeratology lenses (treated eyes), whereas the contralateral eyes were not indicated for visual correction (untreated eyes). The untreated eyes were classified into three subgroups based on the spherical equivalent refraction (SER): low myopia (≤−0.50D, n=37), emmetropia (+0.49D to -0.49D, n=76), and low hyperopia (≥0.50D, n=35). Changes in axial length (AL) were compared between untreated and treated eyes, and among the three subgroups.Results: The axial elongation were 0.14±0.18mm and 0.39±0.27mm in the all treated and untreated eyes, respectively (p<0.001). The interocular AL difference decreased significantly from 1.09±0.45mm at baseline to 0.84±0.52mm at 1 year (p<0.001). The baseline median (Q1, Q3) SER of the untreated eyes were −0.75D (−0.56D, −0.88D), 0.00D (0.00D, -0.25D), and +0.75D (+1.00D, +0.62D) in the low myopia, emmetropia, and low hyperopia subgroups, respectively. The axial elongation was 0.14±0.18mm, 0.15±0.17mm, and 0.13±0.21mm (p=0.92) in the treated eyes and 0.44±0.25 mm, 0.35±0.24mm, and 0.41±0.33 mm in the untreated eyes (p=0.11) after 1 year.Multivariate linear regression analyses only showed significant differences in axial elongation between the emmetropia and low myopia subgroups of untreated eyes (p = 0.04; p>0.05 between other subgroups). This is a provisional file, not the final typeset article 2 Conclusions: Unilateral orthokeratology lenses effectively reduced axial elongation in the more myopic eyes and reduced interocular AL differences in children with myopic anisometropia. The refractive state of the untreated eyes did not affect the axial elongation of the more myopic eye wearing the orthokeratology lens. In untreated eyes, AL increased faster in the low myopia subgroup than in the emmetropia subgroup.